Scaffold-based novel SHP2 allosteric inhibitors design using Receptor-Ligand pharmacophore model, virtual screening and molecular dynamics. (April 2018) - Jin, Wen-Yan; Ma, Ying; Li, Wei-Ya; Li, Hong-Lian; Wang, Run-Ling
Graphical abstract: Highlights: The technique of "Receptor-Ligand Pharmacophore" was used to build the pharmacophore model. 7 potential SHP2 inhibitors were discovered by pharmcophore-based virtual screening and docking analysis. Compared with the SHP099, seven compounds had better conformation in binding to SHP2 in both Docking and Dynamics simulations. Abstract: SHP2 is a potential target for the development of novel therapies for SHP2-dependent cancers. In our research, with the aid of the 'Receptor-Ligand Pharmacophore' technique, a 3D-QSAR method was carried out to explore structure activity relationship of SHP2 allosteric inhibitors. Structure-based drug design was employed to optimize SHP099, an efficacious, potent, and selective SHP2 allosteric inhibitor. A novel class of selective SHP2 allosteric inhibitors was discovered by using the powerful 'SBP', 'ADMET' and 'CDOCKER' techniques. By means of molecular dynamics simulations, it was observed that these novel inhibitors not only had the same function as SHP099 did in inhibiting SHP2, but also had more favorable conformation for binding to the receptor. Thus, this report may provide a new method in discovering novel and selective SHP2 allosteric inhibitors.